2021
DOI: 10.3389/fphar.2020.586498
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol Protects Against Myocardial Ischemia/Reperfusion-Induced Injury by Mediating Apoptosis and Autophagy Crosstalk

Abstract: Many studies have shown that crosstalk exists between apoptosis and autophagy, despite differences in mechanisms between these processes. Paeonol, a major phenolic compound isolated from Moutan Cortex Radicis, the root bark of Paeonia × suffruticosa Andrews (Paeoniaceae), is widely used in traditional Chinese medicine as an antipyretic, analgesic and anti-inflammatory agent. In this study, we investigated the detailed molecular mechanisms of the crosstalk between apoptosis and autophagy underlying the cardiopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Additionally, the mitochondrial anti-apoptotic protein BCL-2 regulates the autophagic process by interacting with BECLIN-1 at the OMM. Protection against I/R damage by the phenolic compound Paenol is related not only carried out with its antioxidant and anti-inflammatory properties, but with increased expression of BCL-2 and downregulation of BECLIN-1, BAX, LC3, and p62, sustaining the hypothesis of crosstalk between apoptosis and autophagy [246]. Additionally, it has been shown that vitamin D, MitoTEMPO or Mdivi-1 treatments reduced COX4 colocalization with LC3 (autophagosomes) in cardiomyocytes subjected to H/R [179].…”
Section: Inhibiting the Mitochondrial Apoptotic Programmentioning
confidence: 89%
“…Additionally, the mitochondrial anti-apoptotic protein BCL-2 regulates the autophagic process by interacting with BECLIN-1 at the OMM. Protection against I/R damage by the phenolic compound Paenol is related not only carried out with its antioxidant and anti-inflammatory properties, but with increased expression of BCL-2 and downregulation of BECLIN-1, BAX, LC3, and p62, sustaining the hypothesis of crosstalk between apoptosis and autophagy [246]. Additionally, it has been shown that vitamin D, MitoTEMPO or Mdivi-1 treatments reduced COX4 colocalization with LC3 (autophagosomes) in cardiomyocytes subjected to H/R [179].…”
Section: Inhibiting the Mitochondrial Apoptotic Programmentioning
confidence: 89%
“…The result showed that paeonol significantly improved cardiac function after I/R. Compared with vehicle treatment, paeonol significantly downregulated the cleaved forms of caspase-8, caspase-9, caspase-3 protein expression, and myocardial I/R-induced autophagy was significantly reversed by paeonol treatment ( 116 ). Similar research showed that paeonol could induce VSMCs autophagy by activating the class III PI3K/Beclin-1 signaling pathway, thus ultimately inhibiting VSMCs apoptosis ( 117 ).…”
Section: Pharmacological Mechanisms Of Paeonol On Atherosclerotic Cardiovascular Diseasementioning
confidence: 99%
“…Paeonol is one of the main compounds present in traditional Chinese medicine, including Moutan cortex, Cynanchum paniculatum , and Paeonia lactiflora Pal. Paeonol is known to exert multiple pharmacological effects, immunomodulation, and liver and kidney protection, antitumor, antipyretic, analgesic, anti-inflammatory, and antibacterial and has been widely used as a nutrient supplement ( Zhang et al, 2019 ; Tsai et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%